Kidnapping the Frisian - Concetta Giliberto (Filologia Germanica)
The several sources documenting the events of the Viking Age in Frisia Magna emphasise the dramatic aspects of the Northern invasions. However, seen from a wider perspective, the FrisianScandinavian relations appear to be multifaceted and at times ambiguous. A number of Old Frisian law texts refer to the Viking practice of capturing and enslaving Frisian men, forcing them to fight on their side, and even sharing spoils with them. A Frisian who undergoes such an experience is called skalk, ‘servant, slave’, a sort of high-ranking servant. He enjoys special rights and even privileges. Such ambiguous status seems the result of the peculiar and not always straightforward interactions between Frisians and Scandinavians.